Study of Recombination and Electric Properties of p-Si Crystals Irradiated with Electrons - Pagava, T.A.; Khocholava, D.Z.; Maisuradze, N.I.; Chkhartishvili, L.S. (Ukrainian Journal of Physics, 2012)
Specimens of p-Si irradiated with 8-MeV electrons have been studied. Various radiation-induced defects have been identified by analyzing the temperature dependences of the hole concentration and the curves of isochronous annealing of irradiated specimens. By analyzing the dependences of the lifetime of minority charge carriers τ, the specific resistance ρ, the hole concentration p, and the Hall mobility μH on the isochronous annealing temperature Tann, the annealing-induced features in the behavior of p and μH are revealed. We determined which radiation-induced defects are recombination centers. From the curves of isochronous annealing carried out during various time intervals, the activation energies of annealing, Eann, are determined for a number of radiation-induced defects.